2009
DOI: 10.1002/jcla.20321
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of serum alpha‐fetoprotein–IgM immune complexes on the diagnosis of primary hepatocellular carcinoma

Abstract: We evaluated clinical significance of serum alpha-fetoprotein (AFP)-IgM immune complexes, in comparison with free AFP, on the diagnosis of primary hepatocellular carcinoma (HCC). Serum levels of AFP-IgM immune complexes and free AFP were determined by the ELISA method and electrochemiluminescence, respectively, in 103 healthy controls, 74 patients suffering from primary HCC, 27 patients suffering from liver cirrhosis, and 63 patients suffering from chronic hepatitis. The best cut-off value of AFP-IgM and free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…For this article, because of the smaller numbers enrolled in a single center, the upper two OGTT glucose strata were combined, leaving six categories of glucose at each of the three time points. In addition, the area under the curve of the maternal OGTT was calculated (13). …”
Section: Methodsmentioning
confidence: 99%
“…For this article, because of the smaller numbers enrolled in a single center, the upper two OGTT glucose strata were combined, leaving six categories of glucose at each of the three time points. In addition, the area under the curve of the maternal OGTT was calculated (13). …”
Section: Methodsmentioning
confidence: 99%
“…1 The discovery of a novel class of tumor markers constituted by circulating IgM antibodies forming immune complexes with specific cancer biomarkers has provided interesting opportunities for HCC patient management. [8][9][10][11][12][13][14][15][16][17][18][19] IgM immune complexes can be detected in the serum of HCC patients as reported for squamous cell carcinoma antigen (SCCA), [9][10][11][12][13]15 for AFP [15][16][17][18] and for DCP, 19 and the assessment of AFP-IgM, DCP-IgM and SCCA-IgM immune complexes has allowed a higher diagnostic performance than the determination of the free, not complexed, biomarker. According to the revised hypothesis of cancer immune surveillance, 20 these immune-complexed biomarkers might be involved in cancer immune-editing, reflecting the host immune-protective mechanisms, aimed at suppressing tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a study reported that HCC patients having anti-p53 autoantibodies had higher survival rate without recurrence (286). In addition, autoantibodies to α-fetoprotein were more prevalent in HCC patients © 1996-2017 than in healthy donors or liver cirrhosis and chronic hepatitis patients (287,288).…”
Section: Role Of Autoantibodies To Self Antigens As Biomarkers For Camentioning
confidence: 99%